Comparison of 5 GB/s WDM Optical System for Different Modulation Format Using Polarization Interleaving Technique. - H. Abdulwahed, Saif; Hameedshakir, Adil; ., Fahamahassoonsalman; A. M. Al-Ja'afari, Mohannad; H. Ali, Ameer (International Journal of Engineering and Technology, 2018)
In this paper investigates a Polarization Interleaving (PI) technique with two modulation format (direct modulation and Carrier Suppressed Return to Zero (CSRZ)) for application in long haul optical system to mitigate the effects of the dispersion and nonlinear. The system is designed with 5 GB/s, 200 Km, 100 GHz channel spacing Wavelength Division Multiplexing (WDM) four channels. The simulation results are validated by analyzing the Quality Factor (Q-factor) versus power and Bit Error Rate (BER) versus Signal-to-Noise Ratio (SNR). It is found that there is an improvement in channels after the PI. For optical direct modulation at 6 dB SNR, an improvement about (0.4 0.8 and 0.6) orders of BER for channel 1, 3 and 4 respectively, while the same performance in channel 2. In CSRZ for the same SNR an improvement of (6.6 4.6 4.8 and 6, 4) orders of BER for channels 1 2 3 and 4 respectively. While in the term of Q- factor of Po=0 dBm. For optical direct modulation in improvement of (2, 3.2 and 0.7) for channel 1, 3 and 4, and there is a reduction in performance to the channel 2about 0.5 Order. An improvement (41.5, 31.7, 39 and 35.7) order of BER for 1,2,3,4 channels respectively. Generally, the threshold power after polarization technique has been improved about (0.5, 10) orders in term of optical direct modulation and CSRZ respectively. All results are expressed in form of BER verses SNR and Q-factor verses power.Â Â